Proceedings of the 2020 ACM/IEEE International Conference on Human-Robot Interaction 2020
DOI: 10.1145/3319502.3374794
|View full text |Cite
|
Sign up to set email alerts
|

Death of a Robot

Abstract: People take to social media to share their thoughts, joys, and sorrows. A recent popular trend has been to support and mourn people and pets that have died as well as other objects that have sufered catastrophic damage. As several popular robots have been discontinued, including the Opportunity Rover, Jibo, and Kuri, we are interested in how language used to mourn these robots compares to that to mourn people, animals, and other objects. We performed a study in which we asked participants to categorize deident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Numerous media outlets reported that households who owned Jibo were devastated by this news and were mourning the loss of a companion (Carmen, 2019;Van Camp, 2019). People on social media used language usually reserved to grieve for humans to describe how they felt about Jibo's fate (Carter et al, 2020). Of course, robots cannot die, and Jibo's discontinuation amounted to the withdrawal of a service that some people had come to value highly.…”
Section: Changing Expectationsmentioning
confidence: 99%
“…Numerous media outlets reported that households who owned Jibo were devastated by this news and were mourning the loss of a companion (Carmen, 2019;Van Camp, 2019). People on social media used language usually reserved to grieve for humans to describe how they felt about Jibo's fate (Carter et al, 2020). Of course, robots cannot die, and Jibo's discontinuation amounted to the withdrawal of a service that some people had come to value highly.…”
Section: Changing Expectationsmentioning
confidence: 99%
“…Children can become very emotionally attached to their robots [22,23]. When the devices stop working, it can create distress [24,25].…”
Section: Emotional Attachmentmentioning
confidence: 99%
“…In order to begin, it was also necessary to review our definition of the term “death.” Namely, whether the destruction of a robot can be described as a death (Carter et al, 2020; Knox & Watanabe, 2018; Lyons, 2018). While there is no consensus in the existing research (nor in our everyday usage) as to whether the word “death” can be applied to inanimate entities, such as a robot, a great deal of research supports the theory that humans can indeed grieve a non-human death or non-death loss.…”
Section: Two Overarching Conceptsmentioning
confidence: 99%